Global, regional, and national epidemiology of thyroid cancer in middle-aged and elderly adults from 1990 to 2021 - Wang, Ling; Liao, LinZhi; Huang, JueZhi; Zhang, Qi; Xiong, YanQing; Tian, FuYu; Liu, Xin; Liu, YanJia; Jiang, LuYun; Xie, Yan (Frontiers in Medicine, 2025)
BackgroundThyroid cancer (TC) has shown dynamic changes in its global burden over the past decades. This study aimed to evaluate trends in incidence, mortality, and disability-adjusted life years (DALYs) of TC among middle-aged and elderly adults across 204 countries and territories from 1990 to 2021.MethodsData were extracted from the Global Burden of Disease Study 2021. Age-standardized rates (ASRs) of incidence, death, and DALYs, estimated annual percentage change (EAPC), and the sociodemographic index (SDI) were used to quantify trends. A Bayesian age-period-cohort (BAPC) model was employed to predict future burden through 2035, and global risk-attributable factors were assessed.ResultsGlobally, TC incidence cases among adults aged 55 and older increased by 185% from 1990 to 2021, with deaths and DALYs rising by 116 and 108%, respectively. The age-standardized incidence rate rose significantly (EAPC = 0.95), while mortality and DALY rates slightly declined. Most regions showed rising incidence, with the exception of Central Europe. Females consistently exhibited higher TC burden, but the gender gap is gradually narrowing. Peak incidence occurred at ages 70–74 for females and 85–89 for males in 2021. High body mass index (BMI) emerged as the leading modifiable risk factor.ConclusionThe rising burden of thyroid cancer in aging populations calls for integrated health policies emphasizing prevention, early detection, and public education. Efforts should focus on reducing modifiable risks, particularly high BMI, and developing age- and sex-specific interventions. Addressing gender disparities and regional inequalities should also be central to global and national cancer control strategies.